Measuring end-user computing sophistication in small-medium enterprises - Md Dahalin, Zulkhairi (Universiti Utara Malaysia, 2003)
This paper describes research on measurement of end-user computing sophistication in the small-medium enterprises. It aims to define and identify an objective measure for EUC Sophistication that can be used by SMEs to assess the extent they are capable of developing their own applications. Measurement for EUC Sophistication was formulated using 3 dimensions of End-User Sophistication, Usage Sophistication and Application Sophistication that form the EUC Sophistication constructs. Using data from an EUC survey study, an instrument was developed to measure EUC Sophistication Index based on the sophistication constructs. Stepwise regression analysis was used to predict the measurement variables based on the data points from the survey using the sophistication index as the dependent variable. Results show that the constructs were valid measurement for EUC Sophistication and among the EUC applications found to be significant include word processing applications, accounts/finance, spreadsheet applications, sales/purchase order, personnel, inventory control, customer, telecommunication, database and decision model.